Applications of the PG(5,q) in coding theory - yahya, Yahya ammar fawzy; yahya, Nada yassen kasm (Iraqi Journal of Science, 2025)
This paper’s primary goal is to present the connection between coding theory and the projective space PG(5,q) of order q, where q=2,3,4,5,7,8,9,11 It was determined whether or not the [n,k,d]-code is perfect. Where n is the length of the code, k is the code dimension, and d is the minimum distance, were calculated with error correction e according to the incidence matrix. We have found that the [n,k,d]-code in PG(5,q), q= 2,3,4,5,7,8,9,11, is perfect if e = 1.